Course of Fecal Calprotectin after mRNA SARS-CoV-2 Vaccination in Patients with Inflammatory Bowel Diseases - Jagoda Pokryszka; Angelika Wagner; Ursula Wiedermann; Selma Tobudic; Harald Herkner; Stefan Winkler; Sonja Brehovsky; Walter Reinisch; Gottfried Novacek (Vaccines, 2022)
Background: Two years into the pandemic, vaccination remains the most effective option to prevent coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Preliminary studies suggest vaccination efficacy in patients with inflammatory bowel diseases (IBD), but little is known about its impact on chronic intestinal inflammation. Here we assessed the mucosal inflammatory activity in patients with IBD before and after immunization with the mRNA-1273 (Moderna) vaccine by measurement of fecal calprotectin (fCP). Methods: In 42 patients with IBD, the baseline fCP levels obtained prior to the first vaccine were compared with the highest levels measured during and after two doses of vaccination. Patients’ sera were collected after the second dose to evaluate anti-SARS-CoV-2 antibodies’ titers. Results: We observed a significant fCP elevation in 31% of patients after any dose. Vedolizumab was identified as the only agent associated with an fCP increase (OR 12.4, 95% CI [1.6; 120.2], p = 0.0171). Gastrointestinal adverse events were reported in 9.5% of all subjects and in 75% of cases accompanied by an fCP increase. Anti-SARS-CoV-2 antibodies associated only weakly with the fCP increase after the first dose (p = 0.04). Conclusions: Our findings support possible collinearity in pathways of SARS-CoV-2 antigen expression and the pathogenesis of IBD.